RELATIVE EFFICACY OF FINE NEEDLE ASPIRATION CYTOLOGY IN DIAGNOSIS OF NODULAR GOITRE - Mubarik, Azhar; Khan, Ahmed Ahson; Nayyar, Shazia; Niaz, Asif (Pakistan Armed Forces Medical Journal, 2006)
Purpose of Study: To evaluate the diagnostic accuracy and limitation of Fine Needle Aspiration Cytology (FNAC) in nodular goiter.Time and Place of Study: The study was carried out at Military Hospital Rawalpindi and the department of Pathology, Army Medical College Rawalpindi from March 2000 to March 2001.Study Design: It was a comparative study.Patients and Methods: 145 patients with nodular goiter who reported to outpatient department were selected for FNAC after taking informed written consent; FNAC was done in department of Pathology of Army Medical College. They were again asked for diagnostic surgery but only 54 patients consented for it. The specimens were studied for histopathology. The data was collected and analyzed by comparison of both procedures by using Gallen and Gambino method.Results: FNAC revealed 44 out of 54 (88.1%) cases as benign and 3 (5.55%) as malignant, while 7 (13%) had indeterminate cytology. All benign lesions were confirmed on histopathology except 01 which turned out to be papillary carcinoma. So FNAC has 98.1% accuracy rate with 92% negative predictive and 100% positive predictive value.Conclusion: FNAC has significant efficacy in differentiating malignant lesions from benign lesions of thyroid. However caution is mandatory in a negative report with strong clinical suspicion of malignancy.